(untitled) (Książnica Śląska, 2025)
Adela Korczyńska was a teacher and scout. For many years she collected materials on women’s underground activities during World War II. These materials currently form her home archive, stored in the Silesian Library. The article discusses a collection of correspondence and divides it into different themes such as private letters, letters related to the collector’s documentary work, original war correspondence (camp letters and secret messages), as well as letters related to the preparation and publication of her texts. It is a fascinating addition to Adela Korczyńska’s biography, revealing her wide circle of friends and acquaintances while providing valuable information about her workshop and methods of work. It also serves as a reminder of the remarkable life of a woman who dedicated herself to documenting the heroic actions of Girl Scouts during the dramatic years of World War II.